Identification and Antimicrobial Susceptibility Pattern of Clinically Significant Coagulase-negative Staphylococci - Nazir, A; Shah, A; Kakru, D; Kadri, S M (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study was undertaken to determine the prevalence and pathogenicity of coagulase-negative staphylococci in clinical samples and to study the antibiotic-sensitivity pattern of the coagulase-negative isolates. Methods: A prospective study was conducted over a period of two years on patients admitted in the Sher-i-Kashmir Institute of Medical Sciences. Blood, urine, pus, catheter tips, cerebrospinal fluid and peritoneal fluid samples of patients who fulfilled the criteria for being labeled as nosocomial were cultured. Results: One hundred and six strains of coagulase negative staphylococci were isolated from the samples and among them 90 isolates were identified as Staphylococcus epidermidis (84.90%). Most of the coagulase-negative staphylococci isolates were resistant to penicillin, cephalosporins and fluoroquinolones. Methicillin resistance was found in a significant number of coagulase-negative isolates. All the isolates were found to be sensitive to vancomycin. Conclusions: The results of the study emphasized that isolation of coagulase-negative staphylococci should be viewed with serious concern and accurate species identification and antimicrobial susceptibility testing should be performed in all cases. DOI: http://dx.doi.org/10.3126/njog.v9i2.11769